Effective temperatures of classical Cepheids from line-depth ratios in the H-band - Kovtyukh, Valery; Lemasle, Bertrand; Nardetto, N; Bono, G; da Silva, R; Matsunaga, N; Yushchenko, A; Fukue, K; Grebel, Eva K. (Monthly notices of the Royal Astronomical Society, 2023)
The technique of line depth ratios (LDRs) is one of the methods to determine the effective temperature of a star. They are crucial in the spectroscopic studies of variable stars like Cepheids since no simultaneous photometry is usually available. A good number of LDR-temperature relations are already available in the optical domain; here we want to expand the number of relations available in the near-infrared (NIR) in order to fully exploit the capabilities of current and upcoming NIR spectrographs. We used 115 simultaneous spectroscopic observations in the optical and the NIR for six Cepheids and optical LDRs to find new pairs of lines sensitive to temperature and to calibrate LDR-temperature relations in the NIR spectral range. We have derived 87 temperature calibrations valid in the [4800-6500] K range of temperatures. The typical uncertainty for a given relation is 60-70 K, and combining many of them provides a final precision within 30-50 K. We found a discrepancy between temperatures derived from optical or NIR LDR for pulsations phases close to ϕ ≈0.0 and we discuss the possible causes for these differences. LDRs in the NIR will allow us to spectroscopically investigate highly reddened Cepheids in the Galactic centre or in the far side of the disc.
Veröffentlicht: 7. Juni 2023
Gesehen am 10.10.2023